2013
DOI: 10.1371/journal.pone.0056858
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Inducibility of the mexXY Multidrug Efflux Operon of Pseudomonas aeruginosa: Involvement of the MexZ Anti-Repressor ArmZ

Abstract: Expression of the mexXY multidrug efflux operon in wild type Pseudomonas aeruginosa is substantially enhanced by the ribosome-targeting antimicrobial spectinomycin (18-fold) and this is wholly dependent upon the product of the PA5471 gene. In a mutant strain lacking the mexZ gene encoding a repressor of mexXY gene expression, expression of the efflux operon increases modestly (5-fold) and is still responsive (18-fold) to spectinomycin. Spectinomycin induction of mexXY expression in the mexZ mutant is, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 40 publications
5
71
0
Order By: Relevance
“…Common mechanisms involved in the resistance observed in PAO1 could be adaptive resistance via the upregulation of the MexXY-OprM efflux pump, 41,50 which is frequently caused by overexpression of the MexY component, or de novo mutations during treatment. 41,51,52 Previous studies have found that a resistance mechanism unrelated to this efflux pump has played a role in aminoglycoside resistance for PAODmutS. 6 Ultimately, molecular studies would identify these resistance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Common mechanisms involved in the resistance observed in PAO1 could be adaptive resistance via the upregulation of the MexXY-OprM efflux pump, 41,50 which is frequently caused by overexpression of the MexY component, or de novo mutations during treatment. 41,51,52 Previous studies have found that a resistance mechanism unrelated to this efflux pump has played a role in aminoglycoside resistance for PAODmutS. 6 Ultimately, molecular studies would identify these resistance mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…5). Their regulators (e.g., MexR, EsrC, ArmZ, and MexT) can respond to various stresses caused by, for example, membrane-damaging or ribosome-disrupting agents, reactive oxygen species, and/or nitrosative stress and subsequently cause increased activities of these pumps against the stresses (441,454,461,467,798,799,827,835,911). Consistently, P. putida RND pump mutants are categorized into 4 functionally distinct subgroups, and one of them is more susceptible to oxidation-inducing agents (912).…”
Section: Bacterial Stress Responsesmentioning
confidence: 92%
“…The very low basal expression level of mexXY(oprA) in wild-type bacteria results from the direct binding of the dimerized, strong repressor MexZ to a 20-bp palindromic sequence encompassing the overlapping promoters of mexXY(oprA) and the adjacent, divergently transcribed gene mexZ (458,825,826). Unlike other TetR-type regulators (727), MexZ's DNA binding is not relieved by antibiotics through a direct ligand-regulator interaction but seemingly via indirect protein-protein sequestration, a process relying on the product of the PA5471 gene, named ArmZ, for the antirepressor of mexZ (825)(826)(827). It was demonstrated that the induction of mexXY expression in response to protein synthesis inhibitors is totally dependent upon ArmZ and that the expression of armZ itself is induced by ribosome-targeting agents through a sophisticated mechanism of transcriptional attenuation involving a short 13-amino-acid leader peptide, PA5471.1 (828).…”
Section: P Aeruginosa Efflux Pumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of mexXY is controlled by the TFR MexZ and requires ArmZ (PA5471) (122), which interacts with MexZ (31,123). armZ encodes a homolog of RtcB, an RNA ligase involved in recovery from stress-induced RNA damage (124), and is cotranscribed with PA5470, which encodes a homolog of PrfH.…”
Section: Tfrs Involved In Regulating Multidrug Resistancementioning
confidence: 99%